2021
DOI: 10.3389/fonc.2021.643382
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapies in Chronic Myeloid Leukemia for Potential Treatment-Free Remission: Focus on Leukemia Stem Cells and Immune Modulation

Abstract: Although tyrosine Kinase Inhibitors (TKI) has revolutionized the treatment of chronic myeloid leukemia (CML), patients are not cured with the current therapy modalities. Also, the more recent goal of CML treatment is to induce successful treatment-free remission (TFR) among patients achieving durable deep molecular response (DMR). Together, it is necessary to develop novel, curative treatment strategies. With advancements in understanding the biology of CML, such as dormant Leukemic Stem Cells (LSCs) and impai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 163 publications
(177 reference statements)
0
21
0
Order By: Relevance
“…Considering these causes of therapy failure, several strategies have been used to overcome drug resistance in CML: (I) the use of drugs targeting the allosteric site of BCR-ABL1 oncoprotein; (II) the use of drugs targeting the ATP site of BCR-ABL1 along with drugs that bind in a different way to Imatinib; (III) the use of drugs, like Asciminib, that target the myristoyl pocket of BCR-ABL1; (IV) the combined use of several TKIs; (V) the use of a TKI in combination with other drugs that target different objectives, such as TKI+IFNα, TKI+chemotherapy, TKI+immune-modulators, etc. [210]; (vi) the use of new TKIs designed to overcome ABL1 gatekeeper mutations (mainly T315I) that at present are only preclinically validated [248]. All these therapeutic approaches are taken in second and third line treatments when initial therapies are not efficient or faint over time due to the emergence of resistance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Considering these causes of therapy failure, several strategies have been used to overcome drug resistance in CML: (I) the use of drugs targeting the allosteric site of BCR-ABL1 oncoprotein; (II) the use of drugs targeting the ATP site of BCR-ABL1 along with drugs that bind in a different way to Imatinib; (III) the use of drugs, like Asciminib, that target the myristoyl pocket of BCR-ABL1; (IV) the combined use of several TKIs; (V) the use of a TKI in combination with other drugs that target different objectives, such as TKI+IFNα, TKI+chemotherapy, TKI+immune-modulators, etc. [210]; (vi) the use of new TKIs designed to overcome ABL1 gatekeeper mutations (mainly T315I) that at present are only preclinically validated [248]. All these therapeutic approaches are taken in second and third line treatments when initial therapies are not efficient or faint over time due to the emergence of resistance.…”
Section: Discussionmentioning
confidence: 99%
“…This culminates into increased Treg levels, T-cell inhibition, and dysfunction of NK cells [202,209]. The relevance of BMM and immunological status in CML was highlighted in TFR studies, where specific immune cell types have been proposed as predictive biomarkers of successful TKI discontinuation [204,210,211].…”
Section: Microenvironment and Immunological Statusmentioning
confidence: 99%
See 2 more Smart Citations
“…Targeted agents targeting the above molecules or pathways have shown promising efficacy in eliminating LSCs by enhancing the killing effect of TKI on LSCs in vitro and vivo studies. Several promising strategies have also entered clinical trials, and some preliminary results showed that TKIs in combination with IFNa, JAK2 inhibitors, PPAR-g agonists, BCL-2 inhibitors, and lysosomotropic agents have the potential to improve treatment response in CML (169,170).…”
Section: Targeting Lscs Via Surface Markersmentioning
confidence: 99%